ANALISIS PERBANDINGAN KUAT TEKAN MORTAR BERDASARKAN MODULUS HALUS BUTIR (MHB) PASIR SUNGAI DENGAN PASIR GUNUNG - Jonrinaldi; Supriani, Fepy; Beriyadi, Agung (Universitas Bengkulu, 2023)
Mortar is a cementation material composed of sand and cement with added water. River and mountain sand are types of sand that are available in large quantities in Bengkulu City. This study aimed to determine the effect of grain fine modulus from river sand on the compressive strength of mortar compared to Curup Mountain Sand. The sand river used was Kembang Sri River Sand (MHB 2,91), Penanding (MHB 2,204), Lubuk Kebur (MHB 3,452), Talang Rasau (MHB 2,257) and Curup Mountain Sand (MHB 1,29). The ratio variation between cement and sand used was 1Pc : 4Ps, 1Pc : 5Ps and 1Pc : 6Ps. Each variation was made 6 cube samples with a side dimension of 50 mm. The test was done at the age of the sample 28 days. The initial flow of the mixture plan is 105-115%. The results obtained of the highest value of mortar compressive strength for the mixture of 1Pc : 4Ps and 1Pc : 6Ps was found in Curup Mountain Sand, which was 14,08 MPa and 7,77 MPa. The highest value of mortar compressive strength for 1Pc : 5Ps mixture was found in Talang Rasau River Sand, which was 11.43 MPa (120,44% compared to Mountain Sand). The 1Pc:4Ps and 1Pc:6Ps mixture of Talang Rasau River Sand has a strength of 87.64% and 93.17% compared to Mountain Sand. Kembang Sri River sand has the lowest mortar compressive strength value for each mixture of 1Pc : 4Ps, 1Pc : 5Ps and 1Pc : 6Ps, compared to the strength of mountain sand was 34,80%, 27,40% and 28,57%. On the average, river sand with the gradation in zone III can be used for mortar mixture, although its strength is still below that of mountain sand. Keyword : river sand, mountain sand, mortar, fine modulus compressive strength.